2007
DOI: 10.1002/mrm.21408
|View full text |Cite
|
Sign up to set email alerts
|

Refining the sensory and motor ratunculus of the rat upper extremity using fMRI and direct nerve stimulation

Abstract: It is well understood that the different regions of the body have cortical representations in proportion to the degree of innervation. Our current understanding of the rat upper extremity has been enhanced using functional MRI (fMRI), but these studies are often limited to the rat forepaw. The purpose of this study is to describe a new technique that allows us to refine the sensory and motor representations in the cerebral cortex by surgically implanting electrodes on the major nerves of the rat upper extremit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 28 publications
4
37
0
1
Order By: Relevance
“…These regions are known to be part of the nociceptive network. Motor cortex activation might originate from antidromic stimulation of the efferent motor fibers as seen in a study by Cho and colleagues [9]. These activated areas are in accordance with those reported for similar studies in rats [53].…”
Section: Discussionsupporting
confidence: 89%
“…These regions are known to be part of the nociceptive network. Motor cortex activation might originate from antidromic stimulation of the efferent motor fibers as seen in a study by Cho and colleagues [9]. These activated areas are in accordance with those reported for similar studies in rats [53].…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, rats under a high current of stimulation may induce activations near the cortical brain regions, such as the S1Tr. Five major peripheral nerves pass through forepaws of rats, the musculocutaneous nerve, the lateral cutaneous nerve, the median nerve, the ulnar nerve, and the radial nerve (Cho et al, 2007). Cho et al found that the cortical BOLD response to direct radial nerve stimulation (1.0 mA, 10 Hz, 1 ms) activated the S1Tr and the secondary somatosensory region (S2).…”
Section: Characteristics Of the Current Functional Pam Systemmentioning
confidence: 99%
“…Similar pulse duration and frequency was applied during direct nerve stimulation, with no effect on the physiological parameters of the animal (Cho et al, 2007).…”
Section: Stimulation Protocolsmentioning
confidence: 99%